Broadband suspended stripline to air‐filled rectangular waveguide transition. Issue 23 (1st November 2015) - Dong, Jun; Peng, Hao; Liu, Yu; Lin, Haodong; Yang, Tao
Abstract : A broadband transition between a suspended stripline (SSL) and a rectangular waveguide is presented. To improve the bandwidth of the transition, a U‐shaped patch is introduced. A back‐to‐back transition prototype has been designed and fabricated for purpose of verification. Experimental results show that the transition has an insertion loss of less than 0.26 dB and a return loss better than 18.5 dB over the entire Ka‐band (26.5–40 GHz), which agrees well with the simulated results. As compared with the SSL‐to‐waveguide transition using a reduced‐height waveguide, the fractional bandwidth is increased from 29.5 to 40.9%. Moreover, with the reduced‐height waveguide removed, the circuit structure has been simplified. The proposed transition provides a good performance while maintaining a simple circuit structure.